Analisis Kualitas Layanan Website Room Menggunakan Metode Webqual dan Importance-Performance Analysis - Meiliana Adeputri Shianto; Sudirman; Afifah (STMIK KHARISMA Makassar, 2023)
Manual registration and attendance processes often lead to long queues and unsystematic archiving sometimes makes it difficult for activity managers to manage data. To overcome this problem, Room service is designed to make it easier for users to carry out the registration and attendance process, participants can register through a 'room' that has been opened by the event organizer which will generate a qr code. The service can be accessed via https://room-idn.com/. After the release, the developer does not know whether the services provided have met the needs and expectations of users or not. Therefore, an analysis of user satisfaction was carried out with a webqual approach to measure the level of satisfaction based on user perceptions. The results showed that the dimensions of usability, information quality, and interaction were of good quality. However, after conducting further research with gap analysis and Importance-Performance Analysis shows that good quality services do not necessarily meet user satisfaction and still need development.